[PP.10.11] RADIOFREQUENCY RENAL SYMPATHETIC DENERVATION IN PATIENTS WITH RESISTANT ARTERIAL HYPERTENSION – 12-MONTH FOLLOW-UP. (September 2016) - Madaric, J.; Vulev, I.; Flak, L.; Skultetyova, D.; Hladikova, D.; Madaricova, T.; Toth, M.; Vaskova, J.; Drangova, E.; Mikulas, J.
Abstract : Objective: To evaluate safety and efficacy of radiofrequency renal sympathetic denervation (RDN) in patients with resistant arterial hypertension (AH) in mid-term follow-up period. Design and method: In the group of 21 patients (54 ± 10 years, M:F 13:8) with inadequately controlled AH on 3 or more antihypertensives including diuretics (average office blood pressure /BP/ 187/112 > mmHg with average number of antihypertensive drugs 7 ± 1), we realized RDN intervention with the use of Symplicity (Medtronic) or EnligHTN (St. Jude) catheters. During the 12-month follow-up we analyzed changes in office BP, ambulatory BP monitoring (ABPM), and presence of complications after intervention. As responders to RDN were defined patients with decrease in office systolic (s)BP > 10 > mmHg. Results: Global or local complications linked to intervention were not detected. The change in renal filtration did not occur, and we did not register renal artery stenosis on control CT angiography after 3 months. One patient died 11 months after RDN due to acute myocardial infarction. In 20 observed patients a significant decrease in office BP 12 months after RDN was present (sBP 187 ± 20 vs 162 ± 32 > mmHg, p = 0.002; dBP 112 ± 20 vs 97 ± 20 > mmHg, p = 0.0006), however only a borderline decrease of ABPM values was reached (sTK 169 ± 16 vs 163 ± 30 > mmHg, p = 0.13). Target decrease in office BP 12 months after RDN was achieved in 15/20 patients (75%). The number or dosage of antihypertensive drugs were reduced in 10/20 patients (50%). In the subgroup of 11 "super-responders" (55%) the decrease in office sBP > 20 mmHg, and ABPM sBP > 15 mmHg was achieved, with average drop in office BP −51/−26 > mmHg and ABPM −23/−9 > mmHg. Responders were characterized by higher office sBP before RDN (191 ± 21 vs 175 ± 15 > mmHg, p = 0.04), lower night-time ABPM before RDN (149/80 vs 165/97 > mmHg, p < 0.05), and by a higher number of ablation points (12.5 ± 2.7 vs 10.2 ± 1.1, p = 0.009), compared to non-responders. Conclusions: Radiofrequency RDN is a safe method of achievement decrease in BP in patients with resistant AH. Higher office sBP, lower night-time ABPM values, and higher number of ablation points are important predictors of RDN clinical success. An increase in number of responders could be expected after the introduction of a newer generation of ablation catheters.